Ensuring the Security and Privacy of Data in Wireless Sensor Intelligence Networks While Simultaneously Optimizing Usability and Efficacy - Kalkar, Parag; Katoch, Gaurav; Sehrawat, Rasna; Sahoo, Deepali Rani; Saravanakumar, AR .; Singh, Arjun; Mishra, Pankaj Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
It is critical to ensure data privacy and security in wireless sensor intelligence networks (WSINs).A comprehensive strategy is needed to balance data security, privacy, usability, and efficacy. It is crucial to achieve the ideal balance between protecting confidential data and ensuring the WSIN serves its intended purpose while adhering to privacy and legal standards. However, can be balanced with optimizing usability and efficacy. This paper explores existing approaches to achieving this balance and proposes a HPSOGA Algorithm to get optimal solution to a variety of security issues by replicating natural behaviours and processes.